Energy and global climate change : bridging the sustainable development divide - Cherian, Anilla (Chichester, West Sussex, UK ; Hoboken, NJ, USA : Wiley Blackwell, 2015)
"This book, is exactly the expansion of the concept of energy access for poor in terms of its linkages with climate change and sustainable development that is the main focus of investigation. In this regard, the argument that is advanced is not whether and how to increase energy access for the poor, or whether and how to improve the prospects for a comprehensive climate change agreement, but instead to ask whether and how energy access for the poor has been factored into the series of key UN led intergovernmental climate change and sustainable development outputs"--
Confronting the neglected nexus between climate change and energy access for the poor -- Where is the "energy" in global climate change negotiations outcomes? : examining key UN global climate change outcomes from 1992-2014 for references to nexus between climate change and energy access for the poor -- Where's the "energy" in key UN global outcomes on sustainable development? : examining the record of UNCHE 1972-Rio+20 2012 for references to nexus between climate change and energy access for the poor -- Understanding the acronym soup of voluntary initiatives and partnerships on sustainable development within the UN content : locating energy access and climate change voluntary efforts -- Towards an integraged framework on energy access for the poor and climate change : issues to consider for the UN led post-2015 development agenda.
Includes bibliographical references.
Description based on print version record and CIP data provided by publisher.
Keywords: Environmental policy -- Developing countries; Poor -- Energy assistance -- Government policy -- Developing countries; Climate change mitigation -- Social aspects; Climate change mitigation -- International cooperation; Energy policy; SCIENCE / Earth Sciences / Meteorology & Climatology; Electronic books